PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE DISERTAI MEDIA GAMBAR TERHADAP HASIL BELAJARBIOLOGI SISWA KELAS VII PADA MATERI KLASIFIKASIMAKHLUK HIDUP DI SMP NEGERI 1 BANGUN PURBA KABUPATEN ROKAN HULU - Purnamasari, Yesi; Lestari, Rena; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aim studyofthis research is to know the result of students studiying at class VII SMP Bangun Purba with applying Think Pair share (TPS) stretegy helped by picture media. The kind of this research is quasi experimental. The sample in this research was the student of VII class 1 and 2 of SMP N Bangun Purba. The research was conducted in November 2014. It can be seen from average score experimental class has average score 76,136 with the highest score is 85 and lowest score is 60. While the average of controll class is 70,47 with the highest score 85 and the lowest score is 60. Based on the hypothesis testing, the value of to higher than t hitung > t tabel is 2,455 > 2,054 It can be con cluded that there is the affect of TPS strategy helped picture media toward the result of students studying of VII SMP class of 1 Bangun Purba school year 2014/2015